Scaling of the Coulomb energy due to quantum fluctuations in the charge on a Quantum dot - Molenkamp, Laurens W.; Flensberg, Karsten; Kemerink, Martijn (Physical review letters, 1995)
The charging energy of a quantum dot is measured through the effect of its potential on the conductance of a second dot. This technique allows a measurement of the scaling of the dot's charging energy with the conductance of the tunnel barriers leading to the dot. We find that the charging energy scales quadratically with the reflection probability of the barriers. The observed power law agrees with a recent theory.